2019
DOI: 10.3906/tar-1805-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual tree measurements in a planted woodland with terrestrial laser scanner

Abstract: Introduction Forest structural diversity is considered to be one of the most important components of biological diversity because it affects the ecological factor beneath the canopy and creates suitable niches for fauna. Therefore, more complex structures indicate greater biodiversity (Szmyt, 2014). Forest structure is also accepted as one of the main naturalness traits, which may include tree density, vertical heterogeneity, canopy cover, and forest layering (Winter, 2012). Hence, quantitative tree and stand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Using TLS, Pazhouhan et al (2017) saw a strong relationship between the two methods with an R 2 value of 0.98 for DBH in the Hyrcanian forest. Similarly, Yurtseven et al (2019) found an R 2 value of 0.99 for DBH in Istanbul, Turkey. In another study, Akgül et al (2016) reached an R 2 value of 0.97 for the same measure in Istanbul too.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Using TLS, Pazhouhan et al (2017) saw a strong relationship between the two methods with an R 2 value of 0.98 for DBH in the Hyrcanian forest. Similarly, Yurtseven et al (2019) found an R 2 value of 0.99 for DBH in Istanbul, Turkey. In another study, Akgül et al (2016) reached an R 2 value of 0.97 for the same measure in Istanbul too.…”
Section: Discussionmentioning
confidence: 81%
“…First, scanning from a fixed position limits usage due to obstructed areas behind large trunks and branches (Leeuwen and Nieuwenhuis, 2010;Bauwens et al, 2016). This so-called occlusion effect may be overcome by scanning from multiple points as Yurtseven et al (2019) did on a forest plot -but it is almost impossible in an FI survey (Oveland et al, 2018), as hundreds of plots are sampled for only one forest enterprise. Other limitations embedded within TLS are its weight as well as equipment acquisition cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 87, only 15 studies worked in the savanna biome [39,145,146]. The most frequently employed methods to derive vegetation attributes are the RANdom SAmple Consensus (RANSAC) algorithm for extracting DBH, stem curve profiles and the detection of stems [97,147], the use of the highest z coordinate of the point cloud for estimating heights [61,148], voxel-based and radiative transfer models for assessing LAI [149,150], Canopy Height Models (CHMs) for delineating crown attributes [91,92], and Quantitative Structure Models (QSMs) for computing tree volume and branch parameters [151,152]. Popular software packages to implement and work with these methods are Lastools [153], Matlab [154], R [155] and Python Programming [156], Cyclone [157], FARO Scene [158], RiscanPro [159], CompuTree [160] and Cloud Compare [161].…”
Section: Methods Used With Tls Point Cloudsmentioning
confidence: 99%
“…Similarly, Calders et al [40] and Chen et al [167] obtained R 2 values of 0.97 when using least squares circle fitting for DBH estimation with a multi-scan TLS scan with 5 positions in a eucalypt open forest and boreal forest respectively. Yurtseven et al [148] obtained an R 2 value of 0.99 with a multi-scan with 8 positions in a Mediterranean forest employing randomised hough transformation with least square regression. In general, multiple TLS scans and a lower stem density yielded the best results [114,168,169].…”
Section: Vegetation Parameters Extracted From Tls Datamentioning
confidence: 99%